The Islamic Principles of Legal Status Criteria according to the Qurʾan and Hadith in Fostering Ḥalāl Vaccine Certification in Malaysia - Latiff, Johari Ab (Al-Bayān, 2024)
In Malaysia, there is a need to provide ḥalāl certification for vaccine products. In 2019, the Department of Islamic Development Malaysia (JAKIM), together with other relevant government agencies and the pharmaceutical industry, improved and expanded the scope and standards of Malaysian Standard MS 2424 Halal Pharmaceuticals-General Requirements, which serves as a general reference for ḥalāl pharmaceutical and vaccine products. It is a step in the right direction. However, ḥalāl certification for vaccine products cannot be implemented due to the lack of a clear legal framework based on Islamic principles derived from Qurʾan, Hadith, and other related legal sources. Furthermore, before this, the status of vaccine products was established through fatwas issued by the authority and not through the ḥalāl certification process. This is because, if ḥalāl certification is given to vaccine products, there may be public rejection of vaccine products that do not have ḥalāl certification, and this could occur during a public health emergency. The objective of this study was to analyse the Islamic principles in determining the ḥalāl vaccine certification. To achieve this objective, qualitative approaches have been used in this research. Data were collected through document analysis and semi-structured interviews with individuals directly involved in the ḥalāl vaccines sector in Malaysia. The findings of this study show that, in implementing ḥalāl vaccine certification, there are several Islamic principles based on Qurʾan and Hadith that can be used in the certification of ḥalāl vaccine products. These include the Principle of Ḥalāl Substances, Ḍarūrah, Maṣlaḥah, Iḥtiyāṭ, Istiḥālah Tāmmah, Istiḥlāk and Fatwā.